2006
DOI: 10.1111/j.1468-3083.2006.01784.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of intermittent isotretinoin treatment in mild or moderate acne

Abstract: Intermittent isotretinoin treatment was found to be a safe and effective choice for patients with mild or moderate acne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 26 publications
(29 reference statements)
1
49
0
4
Order By: Relevance
“…The effectiveness of ISO treatment diminished [8,9] in line with hormonal changes in the intermittent-dose group, which suggests that a cumulative dose of ISO may be important for these hormonal changes. These changes in various hormone systems may be one of the mechanisms of action of ISO treatment.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The effectiveness of ISO treatment diminished [8,9] in line with hormonal changes in the intermittent-dose group, which suggests that a cumulative dose of ISO may be important for these hormonal changes. These changes in various hormone systems may be one of the mechanisms of action of ISO treatment.…”
Section: Discussionmentioning
confidence: 71%
“…There are a lot of different low-dose regimens used in literature, such as daily, intermittent therapy, alternate-day therapy or gradually increasing the daily dose. In these treatment modalities, the mostly frequently used dose of ISO is 0.5 mg/kg/day [4,5,6,7,8,9,10]. In intermittent-dose regimens, the treatment dose is 0.5-1 mg/kg/day; the patients are exposed to a lower cumulative dose, and the medications are not taken every day.…”
Section: Introductionmentioning
confidence: 99%
“…Kaymark and Ilter evaluated 60 patients, 34 women and 26 men, between 18 and 33 years of age [8]. These individuals had discrete-to-moderate acne located on the face.…”
Section: Material Methods and Resultsmentioning
confidence: 99%
“…Moderate cases received 0.6-0.75 mg/kg/day and mild cases received 0.5 mg/kg/day [8]. Some 41 (68.3%) of the 60 patients completed the treatment.…”
Section: Affiliationsmentioning
confidence: 96%
“…Kaymak and Ilter [11] showed the efficacy of the intermittent regimen (0.5-0.75 mg/kg daily for 1 week out of every 4 weeks for a total period of 6 months) in the treatment of 60 patients with mild-to-moderate acne. Amichai et al [12] reported successful treatment of 638 patients with moderate acne with low-dose regimen (0.3-0.4 mg/kg daily for a total period of 6 months).…”
Section: Resultsmentioning
confidence: 99%